Analysis of the Effect of the Implementation of Green Accounting and Environmental Performance on The Financial Performance In Manufacturing Companies - Tri Pratiwi, Endang; Alimuddin, Alimuddin; Mediaty, Mediaty (Dinasti Publisher, 2025)
Green accounting is not just a tool for compliance with environmental regulations, but it can also serve as a strategy to improve a company's financial performance. This study aims to explore the effect of the application of green accounting and environmental performance on the financial performance of manufacturing companies. The population of this study is 91 manufacturing companies in the basic and chemical industry sub-sectors listed on the Indonesia Stock Exchange in 2019-2022. The purposive sampling technique was chosen in this study to determine a sample with a total of 9 companies that met the criteria. The data collection method was carried out in the form of a documentation study through the financial statements and sustainability reports of each company and analyzed using multiple linear regression analysis. The results were obtained that green accounting has a positive and significant effect on financial performance, while environmental performance has a negative and significant effect on financial performance. However, simultaneously, the green accounting variable and the environmental performance variable have a positive and significant effect on financial performance. Thus, companies that invest in environmentally friendly practices not only fulfill their social responsibilities, but also reap significant financial benefits.